EFFECTIVE WAYS TO ORGANIZE PHYSICAL EDUCATION AND MASS SPORTS ACTIVITIES AMONG FEMALE STUDENTS - Abdamitova Kamola Komildjonovna (Modern American Journals, 2025)
The article explores effective methods of organizing physical education and mass sports activities among female students. It highlights the importance of developing motivation for regular physical exercise, promoting a healthy lifestyle, and increasing girls’ participation in sports. The study emphasizes the use of innovative and inclusive approaches that consider students’ physical abilities and social factors.
Keywords: Female students, physical education, mass sports, healthy lifestyle, motivation, gender equality